Cages - Kehret Peg 1936; Peg Kehret (New York : Scholastic, 2002)
After losing an acting role and fighting with her alcoholic stepfather, Kit is arrested for shoplifting and ordered to work, as part of her sentence, at an animal shelter.
M
660
M